Estimating the Radiation Dose to the Fetus in Prophylactic Internal Iliac Artery Balloon Occlusion: Three Cases - Kentaro Kai; Tomohiro Hamada; Akitoshi Yuge; Hiro Kiyosue; Yoshihiro Nishida; Kaei Nasu; Hisashi Narahara (Case Reports in Obstetrics and Gynecology)
Background. Although radiation exposure is of great concern to expecting patients, little information is available on the fetal radiation dose associated with prophylactic internal iliac artery balloon occlusion (IIABO). Here we estimated the fetal radiation dose associated with prophylactic IIABO in Caesarean section (CS). Cases. We report our experience with the IIABO procedure in three consecutive patients with suspected placenta previa/accreta. Fetal radiation dose measurements were conducted prior to each CS by using an anthropomorphic phantom. Based on the simulated value, we calculated the fetal radiation dose as the absorbed dose. We found that the fetal radiation doses ranged from 12.88 to 31.6 mGy. The fetal radiation dose during the prophylactic IIABOs did not exceed 50 mGy. Conclusion. The IIABO procedure could result in a very small increase in the risk of harmful effects to the fetus.